2020
DOI: 10.1111/jgs.16717
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Effects of Caregiver Grief in Dementia and the Modifying Effects of Social Services: A Prospective Cohort Study

Abstract: BACKGROUND: Caregivers of persons with dementia (PWD) can experience loss and grief long before the death of the PWD, with such caregiver grief postulated to affect the well-being of the PWD-caregiver dyads. However, the longitudinal effects of caregiver grief and the moderating effects of social services are not yet clear. OBJECTIVES: We investigated the longitudinal effects of caregiver grief on caregiver depression, caregivers' quality of life (QoL), and caregivers' perceived positive aspects of caregiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…Taking care of AD patients is difficult and is often associated with a high burden of care, especially over a prolonged period of time (van den Kieboom et al, 2020 ). The burden of caregiving can reduce the quality of life of caregivers and cause depressive symptoms (Liew et al, 2020 ). A high care burden typically also reduces the work productivity of caregivers (Fujihara et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Taking care of AD patients is difficult and is often associated with a high burden of care, especially over a prolonged period of time (van den Kieboom et al, 2020 ). The burden of caregiving can reduce the quality of life of caregivers and cause depressive symptoms (Liew et al, 2020 ). A high care burden typically also reduces the work productivity of caregivers (Fujihara et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Marwit–Meuser Caregiver Grief Inventory—Brief-Form (MM-CGI-BF) is a six-item self-report questionnaire assessing grief in caregivers of PLWD (i.e. losses, including anticipation of future losses) on a scale of 1–5 (Liew et al, 2020). Higher scores indicate higher levels of grief.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate higher levels of grief. The MM-CGI-BF has good internal consistency, test-retest reliability, and construct validity in caregivers of PLWD (Liew et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the loss of highly significant relationships following death, which set into motion the grief and mourning processes, recent studies have showed the presence of grief among caregivers in various conditions. These include caregivers of people suffering from major neurocognitive disorder (Dementia) (Chan et al, 2013;Lindauer and Harvath, 2014;Liew et al, 2020;Meichsner et al, 2020;Manevich et al, 2021), Brain Injury (Marwit and Kaye, 2006;Petersen and Sanders, 2015;Yehene et al, 2021), and Disorders of Consciousness (de la Morena and Cruzado, 2013;Yehene et al, 2020), etc. However, despite the significant contribution of these studies, less is known about the mechanisms and processes underlying psychological reactions to such acquired NoDIL and what is the nature of the grief and mourning that follow in their wake.…”
Section: Introductionmentioning
confidence: 99%